Effects of an Engineered Anti-HER2 Antibody chA21 on Invasion of Human Ovarian Carcinoma Cell In Vitro - Gao, Yi (Springer-Verlag Berlin Heidelberg, 2011)
OBJECTIVE: HER-2 plays an important role in the development and progression of ovarian carcinoma. A number of monoclonal antibodies (MAbs) and engineered antibody fragments (such as scFvs) against the subdomain II or IV of HER-2 extracellular domain (ECD) have been developed. We investigated the effect of chA21, an engineered anti-HER-2 antibody that bind primarily to subdomain I, on ovarian carcinoma cell invasion in vitro, and explored its possible mechanisms. METHODS: Growth inhibition of SK-OV-3 cells was assessed using a Methyl thiazolyl tetrazolium (MTT) assay. The invasion ability of SK-OV-3 was determined by a Transwell invasion assay. The expression of matrix metalloproteinase-2 (MMP-2) and its tissue inhibitors (TIMP-2) was detected by immunocytochemical staining, and the expression of p38 and the phosphorylation of p38 were assayed by both immunocytochemistry and Western blot. RESULTS: After treatment with chA21, the invasion of human ovarian cancer SK-OV-3 cells was inhibited in dose- and time-dependent manners. Simultaneously the expression of p38, phospho-p38, MMP-2 and the MMP-2/TIMP-2 ratio decreased, while TIMP-2 expression increased. Additionally, the decrease in phospho-p38 was much greater than that of p38. CONCLUSION: chA21 may inhibit SK-OV-3 cell invasion via the signal transduction pathway involving MMP-2, TIMP-2, p38 and the activation of p38MAPK.